Use of Short Stories in Language Learning - Kadel, Purna Bahadur (Curriculum Development Journal, 2021)
This study is an attempt to explore understanding of English teachers on the use of traditional short stories in language learning and find out the impacts of extensive reading of culturally embedded short stories in consolidating students' language learning. Phenomenological research design was adopted to carry out this study in which 8 English teachers represented 4 from public and 4 from institutional secondary schools were selected from Kirtipur Muncipality of Kathmandu district through purposive non-random sampling procedure. In-depth-interview and classroom observation were used as tools to collect data to address the objectives of this study. The findings of this study show that the language functions and vocabulary could be improved through short stories; language skills could be cultivated with the help of reading short stories; their higher order thinking skills are developed reading short stories; and they get entertainment, motivation and refreshment.